Personal, social, and environmental correlates of physical activity and sport participation in an adolescent Turkish population - TİMURTAŞ, EREN; DEMİRBÜKEN, İLKŞAN; POLAT, MİNE GÜLDEN (My University, 2022)
Background: Benefts of physical activity has been shown for adolescents; however, there is a decline trend in number of adolescents meeting current WHO recommendations. This trend underlines the importance of identifying factors associated with adolescents’ physical activity level (PAL) with considerations of regional and cultural diferences to plan and implement efective policies. Therefore, the aim of this study was to determine personal, ecological, and social factors associated with PAL and sport participation in Turkish adolescents aged 11–14 years. A cross-sectional study was conducted by including 996 adolescents aged between 11 and 14 years from 39 secondary schools in İstanbul, Turkey. Logistic regression analyses performed to identify the signifcant personal (age, gender, sleep time, screen time, BMIz score, having siblings), ecological (presence of playground, type of school transportation), and social (family income, engaging a physical activity with family, and preferred activity at school breaks) predictors of PAL and sport participation. Results: Adolescents who were active during break time at school (p < 0.001), engaging a physical activity with family (p < 0.001), and did not have a sibling (p = 0.029) were more likely to be physically active. Adolescents behaved active during break time at school (p < 0.001), had a playground at home (p < 0.001), spending time with family for physical activity (p < 0.001), and did not have a sibling (p = 0.021) were more likely to participate in a sport activity. Conclusions: Predictors of PAL in this study indicates the need to promote active break time in school, increased physical activity time with family, and to design environmental policies to increase number of playgrounds.
Keywords: Adolescent; Correlates; Physical activity; Sports